Validation of the Grace Risk Score to Predict In-Hospital and 6-Month Post-Discharge Mortality in Patients with Acute Coronary Syndrome - Neves,Vítor Boniatti (2022)
Abstract Background The wide range of clinical presentations of acute coronary syndrome (ACS) makes it indispensible to use tools for risk stratification and for appropriate risks management; thus, the use of prognosis scores is recommended in the immediat clinical decision-making. Objective To validate the Global Registry of Acute Coronary Events (GRACE) score as a predictor of in-hospital and 6-month post-discharge mortality in a population diagnosed with ACS. Methods This is a prospective cohort study of consecutive patients diagnosed with ACS between May and December 2018. GRACE scores were calculated, as well as their predictive value for in-hospital and 6-month post-discharge mortality. The validity of the model was assessed by two techniques: discriminative power using the area under the receiver operating characteristic curve (AUC) and goodness-of-fit, using the Hosmer-Lemeshow (HL) test, at the 5% level of significance. Results A total of 160 patients were included, mean age 64 (±10.9) years; of which 60% were men. The risk model showed to have satisfactory ability to predict both in-hospital mortality, with an area under the curve (AUC) of 0.76 (95% confidence interval [CI], 0.57-0.95; p = 0.014), and 6-month post-discharge mortality, with AUC of 0.78 (95%CI, 0.62-0.94), p = 0.002. The HL test indicated good-fit for both models of the GRACE score. Conclusion In this study, the GRACE risk score for predicting mortality was appropriately validated in patients with ACS, with good discriminative power and goodness-of-fit. The results suggest that the GRACE score is appropriate for clinical use in our setting.